PREVENTION OF PLACENTAL DYSFUNCTION IN PREGNANT WOMEN WITH DENTAL PATHOLOGY - Sytnikova, V.O.; Rozhkovska, N.M.; Rozhko, P.D.; Lysenko, V.V.; Nadvorna, O.M.; Likhachov, V.K. (World of Medicine and Biology, 2024)
In pregnant women, due to changes in the microbiota, diet, and insufficient oral hygiene, the level of inflammatory markers increases, which can contribute to the dysfunction of the fetoplacental complex. The aim of the study was to assess the impact of dental pathology in pregnant women on the risk of placental dysfunction. We studied 87 pregnant women, including 57 women with pathology of hard tooth tissues and periodontal tissues and 30 pregnant women without signs of dental pathology. The microbiocenosis of the oral cavity, indicators of hormonal, biochemical and biophysical profile, morphological changes in the placenta were studied. A positive correlation between the indicators of oral infection and periodontal pathology (r=0.58–0.63, p
Keywords: pregnancy; placenta; periodontium; caries; gingivitis; fetoplacental complex; placental dysfunction